EFFORTS TO IMPROVE STUDENTS' MATHEMATICAL COMMUNICATION ABILITIES BY IMPLEMENTING THE THINK-TALK-WRITE (TTW) LEARNING STRATEGY ON PLANE-SIDED SPACE TOPICS OF ELEMENTARY SCHOOL STUDENTS - Hendrikson R Panjaitan; Melda Oktika Ginting; Zulmawati (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This project seeks to improve sixth-graders' mathematics communication abilities and find ways to teach prisms and pyramids at State Elementary School 060912. Classroom Action Research (CAR) was used. The subjects were 27 sixth-graders. The Think-Talk-Write learning technique was used to improve students' mathematics communication skills. Tests and observation were employed in this investigation. Both cycles of this study ended with a mathematics communication skills test. A validator checked the test before administering it. The first cycle survey found that 77.78% of pupils understood writing (moderate), 59.26% understood representation (poor), and 74.07% acquired classical mastery (adequate). The second cycle showed that 88.89% of pupils understood writing, 85.19% understood representation, and 88.89% reached classical mastery. Observers rated the researcher's learning management as good in the first cycle (83.33 points) and good in the second cycle (88.89 points). Learning through the TTW strategy, media additions, more extensive problem-solving procedures in the LAS than in the first cycle, and group size decrease to 3-4 students improved mathematics communication abilities.  According to the above description, the Think-Talk-Write learning technique can improve sixth-grade students' mathematical communication skills when teaching prisms and pyramids at State Elementary School 060912.